Analysis The Role of Integrated Marketing Communication to Maintaining Customer Relationship at Lets Go Kart Malang - Lion, Mega Purnama; Azzuhri, Misbahuddin (Jurnal Ilmiah Mahasiswa FEB, 2012)
The background of this study aims to determine the effect of Integrated Marketing Communications consisting of four dimensions, namely Advertising (X1), Public Relations (X2), Sales Promotions (X3), and Personal Selling (X4) towards Customer Relations (Y) Lets Go Kart Malang. This study used a sample of 100 customer of Lets Go Kart Malang with a specific category, while the sampling technique used purposive sampling. Results of regression showed that integrated marketing communications simultaneously and partially significant influence to the customer relation. Adjusted R2 value of 0.745, which means 74.5% customer relation is influenced by the independent variable examined, while the remaining 25.5% are other variables that were not detected in this research. Â Advertising variable (X1) became dominant variable effect on the customer relation. Keywords: Integrated Marketing Communication, Customer Relationship, Letâ€™s Go Kart.